DEFINISI SENI ACHDIAT K. MIHARDJA DAN APLIKASINYA PADA SENI KRIYA - Sumadi Sumadi (Institut Seni Indonesia Surakarta, 2005)
Karta Mihardja makes an art definition caused by his worry, at that time the cultural art condition and the personality of Indonesian nation in a state of labile. His aim is to form the image of virtuous Indonesian nation the theme â€œartistic definition of Karta Mihardja and his application at fine artâ€ instructed as creation base form fine art (contemporary art), as distinguishment with the tradition of art product in global era.Keyword:artistic, contemporary, tradition